Good University Governance In Higher Education: A Systematic Literature Review And Research Agenda - Islami, Putri (Politeknik Negeri Ambon, 2025)
Good University Governance (GUG) refers to the principles and practices that ensure universities are managed in a transparent, accountable, and effective manner, with a focus on achieving long-term goals and stakeholder well-being. This systematic literature review aims to explore the literature on GUG in higher education. Using 221 research papers published between 1981 and 2024, from 79 publishers and 166 journals, the study categorizes publication outlets, geographical distribution, research methods (qualitative, quantitative, review, and non-empirical), and theories underlying GUG research. The results show that the number of publications has increased significantly since 2005, with contributions from UK journals dominating. Quantitative methods are the most frequently used approach, followed by qualitative methods, while mixed methods are still rarely applied. The Good University Governance and Governance theories are the most widely used theories, reflecting their relevance in understanding good university governance. However, there is a gap in the use of other theories such as risk management and university performance, which are still underutilized in this study. This study makes a practical contribution by offering guidance for university policymakers to adopt good governance principles and a theoretical contribution by identifying research gaps for future studies. Keywords: Good University Governance, Higher Education, Systematic Literatur Review, Research Agenda